Behavior of unconfined steel-fiber reinforced UHPC post high-temperature exposure - Sohit Agrawal; Erika Yulianti; Mugahed Amran; Chung-Chan Hung (Case Studies in Construction Materials)
Ultra-high-performance concrete (UHPC) is renowned for its superior mechanical and durability characteristics. While many studies have focused on thermal effects such as explosive spalling and the compressive and flexural properties of UHPC, there is limited research on its residual uniaxial tensile behavior. Moreover, variations in the heating rates adopted across different studies further complicate the ability to formulate broad, generalizable conclusions. This study aims to address these gaps by systematically investigating the thermal behavior of unconfined steel-fiber reinforced UHPC in line with the ASTM E119 standard fire exposure. Methods such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and mechanical and durability testing were employed to comprehensively assess UHPC's post-fire performance at ambient temperature. Results revealed that by 200 ˚C, portlandite began converting into calcium oxide and water vapor. Simultaneously, levels of calcium silicate hydrate and calcium carbonate rose, indicating continued hydration at elevated temperatures. SEM imaging exposed significant microstructural issues at 300 ˚C, including debonding between fibers and the matrix, alongside microcracking and degradation at the aggregate-cement paste interface. This deterioration correlated with a significant increase in porosity, permeability, and water absorption, particularly at 300 ˚C. Although compressive strength continued to rise, peaking at 300 ˚C, tensile properties only showed optimal performance up to 200 ˚C before declining, demonstrating a differential impact of temperature on UHPC’s mechanical behavior. Despite this, UHPC displayed tensile strain-hardening behavior up to 300 ˚C, with post-peak strain increasing from 0.2 % at ambient temperature to 0.66 % at 300 ˚C. Nevertheless, a 1.5 % volume fraction of steel fibers proved ineffective in restraining explosive failure at temperatures exceeding 300 ˚C.